fx-gx=x

Simple and best practice solution for fx-gx=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for fx-gx=x equation:


Simplifying
fx + -1gx = x

Solving
fx + -1gx = x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add 'gx' to each side of the equation.
fx + -1gx + gx = gx + x

Combine like terms: -1gx + gx = 0
fx + 0 = gx + x
fx = gx + x

Divide each side by 'x'.
f = g + 1

Simplifying
f = g + 1

Reorder the terms:
f = 1 + g

See similar equations:

| -8z+z=5z+8+5z | | m+-3n=7 | | 6+8=5x | | 41+13x=36 | | X+11=7x+35 | | 27x=24x+6 | | -7-5(6-m)=-43+5m | | 5x^2+3-23=0 | | x+61=80+x+55 | | 2x+4x=(5-3y) | | Z=(2-3j)+(5-4j^3) | | 8(n+4)=10(n-10)-2n | | 5x+4=10x | | 2x+4x(5-3y)= | | 30x-5y=40 | | 3(w+2)-5w= | | 9x+6-3x=6+5x+9 | | .5x+.333x+63=30 | | -3(x-6)=-4+5 | | 9(y-3)=7+8y | | z^2-(3-2i)z+(5-i)=0 | | 13/6=-1 | | 80+55=x+51 | | (1-3y+8)=(2+6-4) | | 2x-3=3(x+9) | | 2[w-(4w+20)+12]=2(w+8) | | 9(k+1)-(-7k-7)=15k | | 80+55=53+x | | 6(x+-6)-8(x+2)=-10 | | 5(x)=(2x-2)(m+6) | | 2cosx-sinx=5/4 | | (X^2+9x-3)(X^2+6x-5)= |

Equations solver categories